2002
DOI: 10.1111/1477-8947.00006
|View full text |Cite
|
Sign up to set email alerts
|

Valuing regional geoscientific data acquisition programmes: addressing issues of quantification,uncertainty and risk

Abstract: Geological surveys worldwide are involved with research in support of sustainable mineral resource development. The socio-economic benefits to be derived from these activities, however, continue to raise organisational and government sector questions. Fundamental questions include whether or not the resources committed are appropriate and in economic balance with the total benefits to be derived. Another question concerns the degree to which such services should be funded by the community at large. These quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Australia: Several papers examine the support provided to mining firms through the below-cost provision of geo-scientific data by state or national geological surveys (Scott et al, 2002;Fogarty and Sagerer, 2016). The collection and public provision of these data reduces prospecting and exploration costs for the mining industry.…”
Section: Country-level Assessments Of a Specific Primary Support Measurementioning
confidence: 99%
“…Australia: Several papers examine the support provided to mining firms through the below-cost provision of geo-scientific data by state or national geological surveys (Scott et al, 2002;Fogarty and Sagerer, 2016). The collection and public provision of these data reduces prospecting and exploration costs for the mining industry.…”
Section: Country-level Assessments Of a Specific Primary Support Measurementioning
confidence: 99%
“…Scott et al (2002) addressed the societal value of updated geological information derived from royalties and reinvestment. Reedman et al (2002) observed that geological field surveys required for the production of new geological maps provide benefits from employment, charitable contributions, and their multiplier effects in developed countries.…”
Section: The Role Of Geoscientific Information In Attracting Exploratmentioning
confidence: 99%
“…Anecdotal evidence suggests that updated geoscience information attracts investment, especially from junior exploration companies, and reduces risk at the earliest and riskiest stages of exploration when generally only smaller budgets are available. Empirical evidence was provided by Scott et al (2002), who applied a revealed preference technique using multiple regression to model the effect of age, type, and detail of government scientific data on total exploration dollars spent, to conclude that upgraded data sets accounted for 10% of the variance in proposed mineral exploration expense compared to a 5% contribution from old data sets. In the same study, an expressed preference procedure concluded that the perception of prospectivity at least doubled with the provision of the upgraded data sets.…”
Section: The Role Of Geoscientific Information In Attracting Exploratmentioning
confidence: 99%
“…The ultimate value of geoscientific information to the mineral explorer is different from the value to society (Gilbert, 1981). Scott et al (2002) addressed the societal value of updated geological information derived from royalties and reinvestment. Reedman et al (2002) observed that geological field surveys required for the production of new geological maps provide benefits from employment, charitable contributions, and their multiplier effects in developed countries.…”
Section: The Role Of Geoscientific Information In Attracting Exploratmentioning
confidence: 99%
See 1 more Smart Citation